Massive gene swamping among cheese-making Penicillium fungi - Jeanne Ropars; Gabriela Aguileta; Damien M. de Vienne; Tatiana Giraud (Microbial Cell)
Horizontal gene transfers (HGT), i.e., the transmission of genetic material between species not directly attributable to meiotic gene exchange, have long been acknowledged as a major driver of prokaryotic evolution and is increasingly recognized as an important source of adaptation in eukaryotes. In fungi in particular, many convincing examples of HGT have been reported to confer selective advantages on the recipient fungal host, either promoting fungal pathogenicity on plants or increasing their toxicity by the acquisition of secondary metabolic clusters, resulting in adaptation to new niches and in some cases eventually even in speciation. These horizontal gene transfers involve single genes, complete metabolic pathways or even entire chromosomes. A recent study has uncovered multiple recent horizontal transfers of a 575 kb genomic island in cheese Penicillium fungi, representing ca. 2% of the Penicillium roqueforti’s genome, that may confer selective advantage in the competing cheese environment where bacteria and fungi occur. Novel phylogenomic methods are being developed, revealing massive HGT among fungi. Altogether, these recent studies indicate that HGT is a crucial mechanism of rapid adaptation, even among eukaryotes.